Plano de Ação Articulada (PAR): política sistêmica do PDE o município de Portel no Arquepélago de Marajó - Cardoso, José Carlos Martins (2013)
This thesis analyzes the Joint Action Plan - PAR and its deployment in the action set in the Plan Hall, under the auspices of the size of educational management in the Municipality of Portel in the state of Pará in the period 2007-2010. It also consists in raising the possible interference of the Integrated Planning, Budget and Finance of the Ministry of Education - SIMEC - PAR module, the process of conducting the municipal education.The overall objective of the thesis is to analyze the systemic process of implementation of PAR as strategic management tool municipal educational systems for teaching and its result in the construction of public policy and management of the municipal education of a city, geographically isolated in space Amazon, and the worst results in IDEB - the city of Para Portel in Marajó archipelago.The research methodology is a case study, a qualitative, and is characterized by analytical and comprises a literature review, documentary research and field research on the City of Portel in Marajó Archipelago , providing direct contact with staff or local committees , followed by semi-structured interviews with staff setting-up of the PAR . From the first theoretical-practical inserts revealed a systemic articulated public policy, technical, operational and bureaucratic, with a demand for action beyond the capacity of the municipal entity from the point of view of educational administration